ACUTE MYOCARDIAL INFARCTION WITH CORONARY OCCLUSION WITHOUT ST-SEGMENT ELEVATION: A SYSTEMATIC LITERATURE REVIEW - Vieira, Éliton Martins; Rodrigues, João Vitor Souza; Garcia, Kaila Sâmy Oliveira Soares Peréa; Oliveira, Kevin Santos; Gasparelo, Luiz Henrique (Seven Editora, 2026)
The current paradigm for Acute Myocardial Infarction (AMI), based on the STEMI/NSTEMI dichotomy, fails to identify approximately 30% of acute coronary occlusions (ACO) that do not present with millimeter ST-segment elevation. Objective: To analyze the literature on Myocardial Occlusion (ACO) without ST-segment elevation, comparing its morbidity and mortality and diagnostic criteria with the traditional model. Methodology: Systematic literature review following the PRISMA protocol in the PubMed and SciELO databases (2015-2026), using the terms "Occlusion Myocardial Infarction", "NSTEMI" and "STEMI equivalents". Results: Studies were included that demonstrate that STEMI criteria have a sensitivity of only 43% to 62% for detecting acute occlusion. Patients with non-ST-segment elevation myocardial infarction (NSTEMI-negative) suffer significant delays in catheterization (median > 400 min vs. 41 min in STEMI) and have a 30-day mortality rate of 7.29%, statistically higher than patients without occlusion. New electrocardiographic patterns (Aslanger, De Winter, Precordial Whirlpool) and artificial intelligence show superior accuracy. Conclusion: The transition to the NSTEMI/NOSTEMI paradigm is urgent to mitigate the undertreatment of critically ill patients erroneously classified as low risk.